Anti-inflammatory effects and beneficial effects of the feed additive Urtica cannabina L. in zebrafish. - Wuyun Liu; Huarong Yu; D Gurbazar; D Rinchindorj; Wei Kang; Chelimuge Qi; Hongsong Chen; Xu Chang; Huan You; Yongmei Han; Zhigang Li; Ahmed R G; et al. (PLoS ONE)
Urtica cannabina L. (UL) has been used clinically for centuries because of its anti-inflammatory properties. This study aimed to investigate the underlying mechanisms and anti-inflammatory effects of different UL concentrations in zebrafish. To elucidate UL's anti-inflammatory properties, two inflammation zebrafish models were designed 1) by severing the zebrafish's caudal fin to assess the repairing effect of UL on the tail inflammation, and 2) by inducing lipopolysaccharides (LPS)-mediated intestinal inflammation to assess the protective and reparative effects of UL on intestinal inflammation at the histological and genetic levels. Furthermore, the effect of UL on the LPS-induced intestinal flora changes was also assessed. After caudal fin resection, a scar formed on the tail of the zebrafish, and the area of the caudal fin increased by 1.30 times as much as that of the control group (P < 0.01). Moreover, this tail scar was alleviated after 10 mg/g UL supplementation but not after 30 mg/g UL dose. LPS decreased the feed intake and body weight of the zebrafish; however, these effects were reversed after 10 and 30 mg/g doses of UL. In addition, the LPS treatment also reduced the intestinal goblet cells by 49% in the zebrafish when compared with the control, which was significantly restored after 10 and 30 mg/g UL treatments. At the genetics level, the expression of the pro-inflammatory cytokine genes (TNF-α, IL6, and IL8) showed that 10 and 30 mg/g UL doses could rescue LPS-induced expression. The gut microbiota analysis revealed changes in the abundance of four major bacterial phyla in the 10 and 30 mg/g UL-treated groups, with an increased probiotic Bacteroidota and decreased pathogenic bacteria. These results indicate that UL strongly inhibits inflammation caused by caudal fin removal and LPS-induced inflammatory changes in the zebrafish intensity, suggesting that UL is a feed additive that could be developed to improve resistance to inflammation in livestock.